Risk factors for and prognostic value of multifocal atherosclerosis in patients with diabetes mellitus - S A Gracheva; M S Biragova; A M Glazunova; I I Klefortova; M Sh Shamkhalova; M I Dzhavelidze; T V Soldatova; A V Il'in; M V Shestakova; É F Tugeeva; Iu I Buziashvili (Терапевтический архив, 2014)
AIM. To study the prognostic value of multifocal atherosclerosis (MFA) in patients with diabetes mellitus (DM) at high risk for myocardial ischemia who need coronary angiography (CAG). MATERIALS AND METHODS. The investigation included 148 patients: 25 with type 1 DM (DM1), 73 with type 2 DM (DM2), and 50 without DM who had undergone CAG. Duplex ultrasound scanning of lower limb vessels and brachiocephalic and renal arteries was carried out in all the patients. RESULTS. Involvement of two or more vascular beds was noted in 60% of the patients with DM1, in 68.4% of those with DM2, and in 34% of those without DM (p < 0.05). Regression analysis showed that the risk factors of MFA were defined to be myocardial infarction (MI) in the history (OR=2.4; p=0.02), DM (OR=3.9; p=0.0002), smoking (OR=2.4; p=0.05), elevated creatinine (OR=6.5; p=0.002) and fibrinogen (OR=6.8, p=0.004) levels. Among the DM patients, there were 26.5% of those who had achieved a main assessment criterion (a combined end point (CEP)), such as death, urgent hospitalization for heart failure, nonfatal MI, nonfatal stroke, lower extremity amputation, double creatinine levels, and achievement of end-stage renal failure during a 24-month follow-up. In patients without carbohydrate metabolic disturbances, this indicator was 12% (p=0.01). During the prospective study, a total of 6.1% of patients died in the DM group; all the patients in the non-DM group completed the study. Calculation of survival rates by the Kaplan-Meier method indicated that the DM patients with concurrent atherosclerotic lesion had achieved CEP significantly more frequently than the comparison group. Such differences were absent among the persons without carbohydrate metabolic disturbances. CONCLUSION. The regression analysis has shown that prior MI, DM, smoking, creatinine and fibrinogen levels are factors associated with the development of MFA in the examined groups. In the patients with DM, concurrent atherosclerosis of two or more vascular beds is an important factor for the progression of cardiovascular and renal diseases.